Appropriation level of the Internet use by librarians in solving user inquiries - Hidalgo Madrigal, Mauren (2015)
This investigation pretended to analyze the management and daily use of Internet performed by librarians, seeking to provide guidance and solutions to queries of its users, considering all the potential resources and services that has the network of networks, to support the work librarianship.Aims to raise awareness, mastery and knowledge possessed by graduates of the National University librarians, on the Internet; the use and exploitation that make all applications; search strategies posed in information retrieval; and the type of queries that fail to evacuate through this.The profiles of graduates from professional between 2000 and 2012 and of its members were determined.Were able to establish personal competence on internet, where it was determined that possess a high level of knowledge on the Internet and competencies of information and technology-digital. Professionals also answer a highly significant number of queries using the Internet, especially in specialized searches.